Prevalence of Rotavirus and Adenovirus in children with acute gastroenteritis: a tertiary care hospital data - Merve Aslantaş; Önder Kılıçaslan; Muhammet Mesut Nezir Engin; Nursel Büyük; Handan Ankaralı; Ramazan Cahit Temizkan; Kenan Kocabay; Gülşen Yalçın (SERNEV, 2017)
Introduction: The aim of this study was to determine theprevalence of rotavirus and adenovirus in patients who applied with the complaintof acute gastroenteritis to the emergency department of our tertiary health careprovider hospitals.Methods: 1712patients with the complaint of acute gastroenteritis were included in the studyand the study was done retrospectively from patient records.Results: Stool(faeces) samples have been sent from 1712 patients who applied to emergency serviceswith the complaint of acute gastroenteritis for 3 years. Of these, 17.5% (n=301)rotavirus antigen and 3.5% (n=61) adenovirus antigen were detected as positive.It was observed that 56% (n=203) of the positive cases were male and 44% (n=159)were female. The rotavirus antigen was statistically significantly higher inthe 0-4 age group than the other age groups.Conclusion: Acute gastroenteritisis an important health problem in children. Especially, the frequency ofrotavirus was observed to be higher in children under 4 years of age and inthis age group patients the use of rotavirus rapid diagnostic tests rather thanviral culture methods may be helpful to early diagnosis thus to reduce unnecessaryantibiotic use.